Mergers and acquisitions in the Netherlands - Wakkie, Peter N. (Kluwer Law and Taxation Publishers, 1992)
Mergers and acquisitions in The Netherlands take place almost on a daily basis. This book gives a comprehensive survey of the legal and tax issues related to mergers and acquisitions in The Netherlands. It addresses acquisition of shares, acquisition of assests, the juridical merger, the Merger Code, unfriendly takeover attempts, protective devices, leveraged buyouts, securities legislation, general tax principles, taxation of share transactions and asset transactions and the tax consequences of a juridical merger. This publication serves as a guideline to corporate executives, bankers, lawyers, tax consultants, accountants and other professionals regularly involved in mergers and acquisitions in The Netherlands. The emphasis of the book is placed on practicality and up-to-date information on a wide variety of topics.